2017
DOI: 10.2174/1389450116666150427161743
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targets in Polycystic Liver Disease

Abstract: Polycystic liver diseases (PLD) are a group of genetic disorders initiated by mutations in several PLD-related genes and characterized by the presence of multiple cholangiocyte-derived hepatic cysts that progressively replace liver tissue. PLD co-exists with Autosomal Dominant Polycystic Kidney Disease (ADPKD) and Autosomal Recessive PKD as well as occurs alone (i.e., Autosomal Dominant Polycystic Liver Disease [ADPLD]). PLD associated with ADPKD and ARPKD belong to a group of disorders known as cholangiocilio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 72 publications
2
54
0
2
Order By: Relevance
“…Octreotide and pasireotide, two somatostatin analogs, decrease proliferation of PCK rat CWEC in vitro and inhibit hepatorenal cyst growth in PCK rats in vivo by reducing cAMP levels. Consistently, clinical trials in patients with polycystic liver disease (PLD) and ADPKD showed that octreotide or lanreotide is well tolerated and decreases total liver volume by 4%–6% [13]. …”
Section: Current Therapies For Arpkdmentioning
confidence: 99%
See 1 more Smart Citation
“…Octreotide and pasireotide, two somatostatin analogs, decrease proliferation of PCK rat CWEC in vitro and inhibit hepatorenal cyst growth in PCK rats in vivo by reducing cAMP levels. Consistently, clinical trials in patients with polycystic liver disease (PLD) and ADPKD showed that octreotide or lanreotide is well tolerated and decreases total liver volume by 4%–6% [13]. …”
Section: Current Therapies For Arpkdmentioning
confidence: 99%
“…Accompanying cyst growth and fibrosis, recent reports suggest that inflammation is also present and likely contributes to disease pathogenesis and/or progression [912]. Aside from management of symptoms and liver and/or kidney transplant, no effective pharmacologic therapies exist for CHF/ARPKD [13]. …”
Section: Introductionmentioning
confidence: 99%
“…disorders are results from structural changes of the biliary tree development and (6) also consist a group of genetic disorders that initiated by mutations in many related genes of PLD and characterized by the development of multiple cholangiocyte derived hepatic cysts that with time replace liver tissue (7,8). Current medical therapies for PLD include symptomatic management (9) and surgical interventions (10).…”
Section: Focus On Surgical Techniques From Bench To Bedsidementioning
confidence: 99%
“…3 In cultured cystic cholangiocytes isolated from an animal model of ARPKD, the PCK rat, and from patients with ADPKD, elevated cAMP enhances cell proliferation, accelerates fluid secretion and affects cell cycle progression via its down-stream modulators PKA, EPAC and ERK1/2/MEK. 2, 4, 5 Together, these observations suggest an important role for cAMP machinery in PLD implicating elevated cAMP as a potential therapeutic target.…”
mentioning
confidence: 90%
“…Indeed, hepatic cystogenesis has been associated with: (i) enhanced fluid secretion into the cyst lumen; (ii) increased rates of cholangiocyte proliferation; (iii) structural and functional ciliary abnormalities; (iv) abnormal cell-extracellular matrix interactions; (v) impaired cell cycle progression; (vi) morphological centrosomal defects; (vii) global changes in mRNA, microRNA and protein expression; and (viii) increased levels of intracellular cAMP. 2 Experimental evidence suggests that cAMP controls different mechanisms in PLD including cell proliferation and fluid secretion. Indeed, intravenous administration of secretin, a major agonist of cAMP signaling in cholangiocytes via interaction with the basolaterally located secretin receptor, increases fluid secretion in hepatic cysts of ADPKD patients.…”
mentioning
confidence: 99%